Adaptações no controle postural estático e dinâmico durante a gestação - Moccellin, Ana Silvia (2011)
Pregnancy causes considerable physiologic, hormonal and anatomic changes in women that may affect the lower limbs and trunk movements, lead to instability of postural control and increased risk of falls, causing a direct impact on mother´s health and quality of life. We conducted three studies to examine the changes in static postural control (STUDY I), in dynamic postural control (STUDY II) and the relationship of these changes with quality of life (STUDY III) of 13 pregnant women during the gestational period (G1, G2 and G3), and a control group of 29 non-pregnant women. For static postural control assessment, a force plate (Bertec®) was used and to assess the quality of life was used the WHOQOL-Bref. In STUDY I posturographic tests were applied in four still standing positions, for three trials, with a combination of different visual conditions (eyes open - EO/eyes closed - EC) and support base configurations. The variables analyzed, derived from the center of pressure (COP), were statokinesigram, displacement amplitude, displacement velocity and sway frequency. In STUDY II were analyzed variables of ground reaction force during the stance phase of gait: time and value of the first peak (P1), second peak (P2) and the valley of the vertical component; time and maximum and minimum value found in the anteroposterior horizontal component (max Fy / min Fy) and the difference between the maximum and minimum values in the mediolateral horizontal component ( max min Fx). And in the STUDY III we used data from the first two studies, plus the assessment of quality of life of pregnant women. The results demonstrate that, early in pregnancy, the woman's body seems to be already adapted for postural control, probably due to hormonal factors, and during the trimesters there was a decrease in postural stability. Compared to the control group, pregnant women had larger areas, an increase in the amplitudes and velocities of COP displacement, more time in the first phase of weight acceptance, lower values of peak 1 and 2 of the vertical component and lower maximum and minimum values of anteroposterior horizontal component of ground reaction force, possibly indicating a reduction in speed and thrust of the gait. With respect to quality of life, the physical domain was the most affected in the first trimester, with lower values mainly during late gestation.